Isolation of subunits from Methanosarcina barkeri ATPase: nucleotide-binding site in the alpha subunit. - Inatomi, K (1988)
The alpha (62,000-dalton) and beta (49,000-dalton) subunits of Methanosarcina barkeri ATPase were purified to homogeneity. The subunits and ATPase complex were trypsinized in the presence of various nucleotides. ATP and ADP changed the trypsin sensitivity of the alpha subunit in the complex and isolated forms, suggesting the presence of a nucleotide-binding site in the alpha subunit.